2020
DOI: 10.1097/qad.0000000000002603
|View full text |Cite
|
Sign up to set email alerts
|

First-line HIV treatment outcomes following the introduction of integrase inhibitors in UK guidelines

Abstract: on behalf of the UK CHIC StudyObjective: To investigate the characteristics and outcomes of people who initiated different antiretroviral therapy (ART) regimens during the era of integrase strand transfer inhibitors (INSTIs).Design: UK-based observational cohort study.Methods: UK Collaborative HIV Cohort study participants were included if they had started ART between 1 January 2012 and 30 June 2017. Virological failure was defined as the first of two consecutive plasma HIV RNA more than 50 copies/ml, at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…In fact, also in this study low-level plasma HIV RNA was more frequently detectable in PI-treated than in NNRTI-treated participants, despite no difference in therapy adherence by regimen. Notably, a recent large study of more than 12,000 participants starting ART revealed that PI-treated participants were on average 2.7 times more likely to experience virological failure compared with NNRTI-treated participants [47]. Moreover, three independent clinical trials of triple ART intensification with raltegravir have previously demonstrated much stronger increases in episomal HIV DNA in PI- compared to NNRTI-treated participants, suggesting that at “baseline”, PI-treated individuals had higher levels of residual replication [21, 22, 25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, also in this study low-level plasma HIV RNA was more frequently detectable in PI-treated than in NNRTI-treated participants, despite no difference in therapy adherence by regimen. Notably, a recent large study of more than 12,000 participants starting ART revealed that PI-treated participants were on average 2.7 times more likely to experience virological failure compared with NNRTI-treated participants [47]. Moreover, three independent clinical trials of triple ART intensification with raltegravir have previously demonstrated much stronger increases in episomal HIV DNA in PI- compared to NNRTI-treated participants, suggesting that at “baseline”, PI-treated individuals had higher levels of residual replication [21, 22, 25].…”
Section: Discussionmentioning
confidence: 99%
“…We previously proposed CA RNA as a sensitive marker of the active HIV reservoir and residual replication [6], a role that is further reinforced by the results of this study. Monitoring of CA RNA levels to detect residual HIV activity despite ART is warranted in order to prevent possible ART complications such as persistent immune activation or therapy failure [47, 64, 65], especially in individuals treated with PI-based regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Integrase strand transfer inhibitors (INSTIs) are one of the recommended third agents for initial antiretroviral therapy (ART) regimens [1]. Raltegravir (RAL) and dolutegravir (DTG) remain the most widely used INSTIs in the UK [2]. 'Excessive' weight gain with INSTI-based regimens has been reported in a variety of settings, although the magnitude of the weight gain impact attributable to INSTIs, and what level of change should be considered significant remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, also in this study low-level plasma HIV RNA was more frequently detectable in PItreated than in NNRTI-treated participants, despite no difference in therapy adherence by regimen. Notably, a recent large study of more than 12,000 participants starting ART revealed that PI-treated participants were on average 2.7 times more likely to experience virological failure compared with NNRTI-treated participants [53]. Moreover, three independent clinical trials of triple ART intensification with raltegravir have previously demonstrated much stronger increases in episomal HIV DNA in PI-compared to NNRTI-treated participants, suggesting that at "baseline", PI-treated individuals had higher levels of residual replication [21,22,25].…”
Section: Discussionmentioning
confidence: 99%
“…We previously proposed CA RNA as a sensitive marker of the active HIV reservoir and residual replication [6], a role that is further reinforced by the results of this study. Monitoring of CA RNA levels to detect residual HIV activity despite ART is warranted in order to prevent possible ART complications such as persistent immune activation or therapy failure [39,53,75], especially in individuals treated with PI-based regimens. i Mann-Whitney tests were used for continuous variables and Fisher's exact tests or Chi-square tests were used for categorical variables.…”
Section: Discussionmentioning
confidence: 99%